A Lifestyle Management of Mental Health Decreasing The Stress Level Of Student - Khamida, Khamida; Budury, Syiddatul; Rohmawati, Riska; Fitriasari, Andikawati Fitriasari; Zahroh, Chilyatiz (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Living at boarding school environment requires to approach the environment well. Because of the demands or burdens of some complain of dizziness, fear of not being able to memorize according to the target, unable to concentrate which is a sign and symptom of stressfull. Research aim to find out the relationship between life style management of mental health and stress levels. Study uses Cross Sectional Design, the sample was 153 students taken by simple random sampling. The independent variable was mental health life style management, the dependent variable was the level of stress. The instrument uses a questionnaire. Data analysis with the Spearman's Rho. Results showed p = 0,000, which means there was a relationship between life style management of mental health with stress levels. Life style management it needs to be applied in Islamic boarding schools in order to increase their productivity and stay mentally healthy.